Student Perceptions of the Three-Phase Learning Model in English Courses - Arif, Rifda Nur Hikmahwati (Jambura Journal of English Teaching and Literature, 2026)
This study aimed to analyze student perceptions of the implementation of a three-phase learning model (trigger questions and discussion, lecturer explanation, and practice exercises) in English courses. This research contributes to the pedagogical discourse on active learning approaches by providing empirical evidence of how non-English major students perceive structured, phase-based instruction that combines discussion, direct explanation, and practice. The findings offer insights into which instructional elements resonate most with learners and which require refinement, thereby informing evidence-based improvements in English language teaching for teacher education programs. This study employed a survey method with a quantitative descriptive approach. The research sample consisted of 72 students from the Primary School Teacher Education Program, divided into three classes (A, B, and ICP). The research instrument was a questionnaire with 32 statement items using a 1-5 Likert scale. The instrument reliability was very high, with a Cronbach's alpha of 0.928. The results showed that student perceptions of the three-phase learning model were in the good category, with a mean score of 3.68. The aspects receiving the highest appreciation were the delivery of learning objectives at the beginning of the session (mean score of 4.25) and the relevance of examples to the exercises (mean score of 4.12). Meanwhile, the pace of material delivery (mean score of 3.25) and transitions between phases (mean score of 3.32) require improvement. ANOVA tests showed no significant difference in perceptions among classes (p=0.260), nor did t-tests based on gender (p=0.533).